Performance of Mustard Varieties in haor Area of Bangladesh (Bangladesh Agronomy Journal, 2017)
A varietal trial of mustard was conducted at Noagaon village of Dekhar haor areas of south Sunamganj upazila of Sunamganj district, during November 2015 to March 2016, to find out the suitable mustard variety/varieties. A total of five varieties viz. BADC 1, SAU Sarisha-3, BARI Sarisha-11, BARI Sarisha-14 and BARI Sarisha-15 were tested in the farmer’s field. The experiment was carried out in a randomized complete block design with three replications. Significant differences were found among the mustard varieties for number of branches plant-1, number of capsules plant-1, capsule length, 1000-seed weight and seed yield. The mustard var. BARI Sarisha-11 produced the highest number of branches plant-1, number of capsules plant-1, 1000-seed weight resulting the highest seed yield (1.64 t ha-1), followed by BARI Sarisha-15 (1.47 t ha-1). The seed yield of BARI Sarisha-11 and BARI Sarisha-15 was not differed significantly, but the growth duration of BARI Sarisha-15 was shorter than the others.Bangladesh Agron. J. 2017, 20(1): 1-5